Understanding the multifaceted nature of peptide hydrogels in biomedical research - Srestha Ghosh; Shinjini Chaudhuri; Subhabrata Guha; Gaurav Das (Academia Materials Science)
Hydrogels are networks of three-dimensional cross-linked polymers, which possess the capacity to absorb and retain water. Hydrogels have proven to be adaptable and versatile, making them useful in various biomedical applications such as tissue engineering and regenerative medicine. Among the various types of hydrogels, peptide-based hydrogels are most suited for biological applications due to their special features, which include biodegradability, mechanical stability, biocompatibility, capacity to retain more water, injectability, and elasticity like that of tissues. In this review, we will present the recent advancements that have occurred in the field of peptide-based hydrogels concerning its biomedical applications especially delivery of targeted delivery, wound healing, tissue engineering, stem cell therapy, etc.